Microbial keratitis: A five years retrospective clinical study in tertiary eye hospital of eastern region of Nepal - Puri, Lila Raj; Shrestha, Gauri Shankar (Journal of Kathmandu Medical College, 2017)
Background: Corneal ulcer is a sight threatening disease of significant public health concern. Early diagnosis with microbiological identification of the causative organism and institution of the proper medical therapy are important for successful visual recovery.Objectives: To find out the demographic and predisposing factors associated with corneal ulcers, evaluate management of ulcers on the basis of clinical features and corneal scraping results.Methods: It was a retrospective clinical study conducted among 1897 subjects with microbial keratitis in Sagarmatha Choudhary Eye Hospital, Lahan, Nepal from January 2010 to December 2014. Assessment included detailed eye examination with slit lamp for size, depth and location of ulcer, presenting visual acuity on internally illuminated Snellen’s chart, and corneal scrapings for Gram’s stain and 10% Potassium hydroxide wet mount. A standard treatment was delivered on the basis of clinical features and corneal scraping results. Subjects were evaluated subsequently after 48 hours, one week, two weeks, three weeks and four weeks of initiation of therapy. Non-responding cases were admitted to perform re-scraping and to modify therapy.Results: Majority of subjects (71.2%) belonged to the age group of 26 to 55 years  (71.2%), presented after two weeks (82.3%) and used non-prescription eye drops (71.9%) before visiting to the eye hospital. Ocular trauma (54.5%) was the most commonly reported predisposing factor. The central and paracentral ulcers comprised of 72.8% of ulcers withsize greater than 2mm in 2.7% and moderate ulcer in 71.1%. Microbiological test revealed fungal ulcers in 78.1% subjects. Presenting visual acuity better than 6/18 was reported in 7% only.Conclusion: Corneal ulcer was one of the commonly reported eye disease in Terai region of Nepal. Trauma is the commonest cause of corneal infection. Fungal corneal ulcers werecommonly noted.